Pengukuran Indole- 3-Acetic Acid (IAA) pada Bacillus sp dengan Penambahan L-Tryptopan - Astriani, Meli; Murtiyaningsih, Hidayah (Universitas Muhammadiyah Prof. Dr. Hamka, 2018)
Background: Indole acetic acid (IAA) is a plant growth hormone that has an important role for stimulation growth of plants. The exogenous IAA produced by bacteria is able to accelerate the plant growth in improving process of root differentiation to form root hairs. Rhizosphere bacteria mostly known as a producer of IAA. Bacillus sp is one of rhizosphere bacteria on plants. The aim of this study was to determine IAA content from Bacillus sp by measuring the levels of IAA using colorimetric method. Methods: Stages of this study are as follows: recultures of testing isolates, manufactures IAA standard curve and measures levels of IAA which reacted to Salkowsky reagent. Results: Results showed that IAA content of Bacillus sp which were obtained by adding L- tryptophan was 39.92 ppm. Conclusions: IAA content which produced by Bacillus sp is high enough to be applied as a plant growth promoter bacteria (PGPR).